The Influence of Subjective Norms on Farmers' Behavior in Handling Goat Waste - Baba, Syahdar; Hastang, Hastang; Asnawi, Aslina; Dagong, Muhammad Andi Ihsan; Hendra, Hendra; Indrawirawan, Indrawirawan; Khasanah, Aulia Uswa Noor; Risal, Muhammad; Sohrah, Sitti; Dariyatmo, Iin Mulyawati (Hasanuddin Journal of Animal Science (HAJAS), 2023)
Waste treatment (WT) was one way to increase the income of small-scale goat farmers. Many factors influence breeders to adopt technology, including the subjective norm (SN) factor. This study aims to determine the effect of subjective norms (SN) consisting of the influence of informal leaders (IL), Family (F), extension (E) /Training Officer (TO), and peer groups (FG) or farmer neighbors (FN) on the behavior of farmers in feces waste treatment (WT). The research was carried out in West Sulawesi Province, precisely in Polman and the Majene Regencies, which were goat farming centers. The respondents were 50 in the Majene district and 100 in the Polman district. The determination of the sample was carried out randomly at the location of the goat breeding center (GBC). The research variable consisted of the behavior of farmers in adopting technology (AT), which consisted of five levels: feces disposed of (score 1), not processed and used alone (score 2), not processed and sold (score 3), processed and used alone (score 4). It was processed and sold (score 5). Independent variables consisted of subjective norms, including the Community Leader (CL) (X1), Family (F) (X2), Extension Workers (EW) or Technical Officers (X3), and Neighbors (N) or colleagues (C) influence (X4). The linear regression model was used to predict the F-test and t-test. The results showed that SN affects breeders’ behavior in processing goat livestock waste (GLW). The variable influence of EW, F, and N was a component of SN that influenced the behavior of breeders, to increase the adoption of WT technology, the role of EW must be increased in assisting farmers in adopting WT technology. Keywords: Goat, subjective norm, adoption, extension officer, Family member